Analisis Pengelolaan Air Bekas Wudhu’ Jamaah Mesjid Jamik Lambaro Kabupaten Aceh Besar - Bahagia Bahagia; Muhammad Nizar (Jurnal Serambi Engineering, 2018)
Used water has the potential to be processed and recycled based on its continuous volume and quality that allows processing in place. The need for the importance of water is not balanced with consciousness to conserve water, so that many sources of water are polluted by human actions themselves. The purpose of this study is to determine the level of waste water usage of ablution activities, to know the performance of water treatment using ablution water through a combination of slow sand filter; and analyze the content of BOD5, E.colli / total coliform, pH and ablution water temperature. This research took samples at Jamik Lambaro Mosque, Regency of Aceh Besar, then tested in Environmental Engineering Laboratory of Environment of Serambi Mekkah University. The results showed that the use of ablution water increased at the time of five daily prayers, especially on Friday reached 1,579 people with the use of water ablution reached 4747 liters. Currently, there is no water treatment for the former Mosque of Jami’ Lambaro Mosque, the waste water is dumped into the mosque’s drainage ditch. Based on ablution water treatment with sand combination has decrease efficiency of BOD5 equal to 95%. The results of laboratory tests showed that the BOD5 content of 17 mg / l, its value under the standard quality of 50 mg / l. E.colli / total coliform that is 0 from 100 ml that meets the quality standard in accordance with Kep.Men LH RI No. 5 year 2014. The result of temperature / temperature analyst is 28,9 oC and pH is 7,34